Tradisi Moginum dan Tingkah Laku Kristen Menurut Doktrin Ke-22 GMAHK di Sabah - Au, Benedict; Pardos, Milton T.; Daniel, Elney Viviana (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to examine the relationship between the practice of Moginum in the Rungus community and the teachings of the Seventh-day Adventist Church (SDA), particularly the 22nd Doctrine, which emphasizes the body as the temple of the Holy Spirit (1 Corinthians 6:19). As a cultural tradition rooted in Rungus society, Moginum presents a theological and moral challenge for Adventist members in upholding the principle of bodily sanctity. This research employed a qualitative approach using in-depth interviews and participatory observation among church members in Kuala Parapat, Sabah, Malaysia. The findings reveal that some members continue to engage in Moginum in various forms, while others have abandoned it after gaining a clearer understanding of the church’s teachings. The church has responded by promoting theological education and culturally sensitive pastoral strategies, including the adaptation of Moginum practices without alcohol. These findings highlight ongoing efforts in inculturation and contextualization within religious practice and offer an inclusive approach to engaging local traditions without compromising doctrinal integrity.